Total distance travelled within Tth second is calculated in a certain way. It is done via,

Distance travelled in T seconds- Distance travelled in (T- 1) seconds

In equational form, the same is depicted as,

ST– Se (T-1)

Suppose the value of S0 is 0.

As per equation (1.7),

St = v0 t +  at2

ST =V0 T + At2

S (T-1) = V0 (T-1) +a (T-1)2

ST –S (T-1)

=[v0 T+ a (T)2] – [ v0(T-1) + a (T-1)2]

=v0 T+a T2 – v0T-1 +At -a

= v0 + a (2T -1)

= S Tth = v0 +a (2T -1)


Links of Previous Main Topic:-

Links of Next Mechanical Engineering Topics:-

Submit Your Assignment


Customer Reviews

My Homework Help
Rated 5.0 out of 5 based on 510 customer reviews at
Rating View

Trusted Reviews from Google

Trusted Reviews from trustpilot